Income and Population Growth. (1st September 2014) - Brueckner, Markus; Schwandt, Hannes
Abstract : Do populations grow as countries become richer? In this study we estimate the effects on population growth of shocks to national income that are plausibly exogenous and unlikely to be driven by technological change. For a panel of over 139 countries spanning the period 1960–2007, we interact changes in international oil prices with countries' average net‐export shares of oil in GDP. Controlling for country and time fixed effects, we find that this measure of oil price induced income growth is positively associated with population growth. The IV estimates indicate that a 1 percentage point increase in GDP per capita growth over a 10‐year period increases countries' population growth by around 0.1 percentage points. Furthermore, we find that this population effect results from both a positive effect on fertility and a negative effect on infant and child mortality.